Influence of TiO2 layer's nanostructure on its thermoelectric power factor - Salleh, Faiz; Usop, Rohaida; Saugi, Nur Susilawati; Salih, Ethar Yahya; Mohamad, Mahazani; Ikeda, Hiroya; Sabri, Mohd Faizul Mohd; Ahmad, Mohd Khairul; Said, Suhana Mohd (Elsevier, 2019)
Rutile-phased TiO2 thin films consist of single layer of nanorod structure and bilayer of nanorod and nanoflower structure with thickness of 2–10 μm were synthesized on FTO glass substrate and its Seebeck coefficient and electrical conductivity were measured in order to clarify the influence of layer's structure on its thermoelectric power factor for self-powered smart window material application. The Seebeck coefficient and electrical conductivity of TiO2 thin films were found to be dependent on the type of layer's structure, and to be independent on the thickness of the layer, which is likely due to the elimination of phonon system contribution and its anisotropic dependency. The bilayer TiO2 thin film is found to possess the highest power factor of 79.7 μW/mK2 at 390 K, which is almost three times larger compared with a reported value for oxide material on glass substrate. These show a promising possibility to apply TiO2 thin film as thermoelectric harvester film fabricated on glass window. © 2019 Elsevier B.V.